Let t be a positive integer and n = 2 t + 1 . Define A = i = 0 ∑ t ( i n ) 2 0 1 9 i and B = i = t + 1 ∑ n ( i n ) 2 0 1 9 i .
Compare 2 0 1 9 A and B .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I think your transition to the sum ∑ i = 0 t ( i 2 t + 1 ) 2 0 1 9 i + t + 1 is not entirely correct. What is the coefficient of the term 2 0 1 9 2 t + 1 in B and in ∑ i = 0 t ( i 2 t + 1 ) 2 0 1 9 i + t + 1 ?
(Edit: you had the right idea approaching this problem, only got the notation mixed up. Keep going!)
Log in to reply
You are right. I will change the solution.
Have a closer look at B and define a new counting variable: j = n − i . Then j is from n − ( t + 1 ) = 2 t + 1 − ( t + 1 ) = t to n − n = 0 , while ( i n ) = i ! ( n − i ) ! n ! = ( ( n − i ) n ) = ( j n ) . So B can be rearranged and written as: B = ∑ j = 0 t ( j n ) 2 0 1 9 n − j .
Consider B − 2 0 1 9 A we have: B − 2 0 1 9 A = ∑ j = 0 t ( j n ) 2 0 1 9 n − j − 2 0 1 9 ∑ i = 0 t ( i n ) 2 0 1 9 i = ∑ j = 0 t ( j n ) 2 0 1 9 2 t + 1 − j − ∑ j = 0 t ( j n ) 2 0 1 9 j + 1 (rename the variable in the latter sum from i to j ) = ∑ j = 0 t ( j n ) ( 2 0 1 9 2 t − j + 1 − 2 0 1 9 j + 1 ) .
For any j from 0 to t − 1 we see that 2 0 1 9 2 t − j + 1 − 2 0 1 9 j + 1 > 0 (note the case j = 0 ) while at j = t , 2 0 1 9 2 t − j + 1 − 2 0 1 9 j + 1 = 2 0 1 9 t + 1 − 2 0 1 9 t + 1 = 0 . This ensures ( j n ) ( 2 0 1 9 2 t − j − 2 0 1 9 j ) ≥ 0 for all j ∈ { 0 , 1 , . . . , t } . And because the term j = 0 is present regardless of t , B − 2 0 1 9 A = ∑ j = 0 t ( j n ) ( 2 0 1 9 2 t − j + 1 − 2 0 1 9 j + 1 ) > 0 for all positive integer t , implying B > 2 0 1 9 A .
t = 1 ⟹ 1 ; n = 2 t + 1 ⟹ 3 ; assuming x ≥ 1 , which it is as x = 2 0 1 9 , ( ∑ i = 0 t x i + 1 ( i n ) ⟹ 3 x 2 + x ) < ( ∑ i = t + 1 n x i ( i n ) ⟹ x 3 + 3 x 2 ) . The difference only becomes greater as t becomes larger.
Wolfram, using t=1 meaning n=3
You can see that B is much larger than 2019*A
Problem Loading...
Note Loading...
Set Loading...
B = i = t + 1 ∑ 2 t + 1 ( i 2 t + 1 ) 2 0 1 9 i = i = 0 ∑ t ( i 2 t + 1 ) 2 0 1 9 2 t + 1 − i = i = 0 ∑ t ( i 2 t + 1 ) 2 0 1 9 i + ( 2 t − 2 i + 1 ) > 2 0 1 9 A Note that i = t + 1 ∑ 2 t + 1 ( i 2 t + 1 ) = i = 0 ∑ t ( i 2 t + 1 ) Since 2 t − 2 i + 1 ≥ 1